Current status and future perspectives of the application of Traditional Chinese Medicine nursing for patients with constipation after stroke (中医护理在脑卒中后便秘患者中的应用现状及展望) - MA Xin (马欣); GENG Qingwen (耿庆文); TANG Ling (唐玲); TUO Yuhong (庹玉红); HOU Xueru (侯雪茹) (Association of Integrative Nursing, 2021)
Constipation is a common complication after stroke, affecting the quality of life and threatening lives of patients. The Traditional Chinese Medicine nursing has its unique advantages in prevention and treatment of constipation after stroke. This paper summarized the etiology and pathogenesis of constipation after stroke, and discussed the current status and future perspectives of the application of Traditional Chinese Medicine nursing techniques, in order to provide reference for nursing management of patients with constipation after stroke. (便秘是脑卒中患者常见的并发症, 长期便秘不仅会影响患者生存质量, 严重者还会危及患者生命。中医护理在脑卒中后便秘的防治中有其特色和优势。本文对脑卒中后便秘病因病机、中医特色护理技术的应用现状以及发展展望进行了总结, 旨在为临床脑卒中后便秘患者的中医护理提供参考。)